Micro:bits plate simulator as educational technological tool for digital literacy in Professional Education (Research, Society and Development, 2022)
This article is the result of a pilot project with the objective of providing digital literacy, based on Problem-Based Learning (PBA), in the context of Vocational and Technological Education (VET) with application to the Technical Course of Oil and Gas, through the subject of Programmable Logic Controllers. The following guiding question was used to achieve the objectives proposed in the research: How can the use of Micro:bit board simulators influence the digital literacy process of students in a professional school? From this main question, the research had the elaboration and execution of multiple, interdisciplinary and contextualized projects, which resulted in the strengthening of the students' cognitive and labor activities. In addition to the students, the research brought to light an unexpected aspect, in this case, the need for digital literacy also of the teaching staff as a whole, since professional education brings as a premise the process of integrated education and training.